Kinetic Analysis of Polyvinylpyrrolidone Pyrolysis Using Thermogravimetric Analysis - Abdul Hamid Elghemi (AlQalam Journal of Medical and Applied Sciences, 2026)
Polyvinylpyrrolidone (PVP; poly(N-vinylpyrrolidone)) is a versatile water-soluble polymer widely used in pharmaceuticals, coatings, and nanocomposites due to its solubility, biocompatibility, and film-forming properties. Despite its extensive applications, systematic kinetic data describing its thermal degradation remain limited. In this study, non-isothermal thermogravimetric analysis (TGA) of PVP was performed under nitrogen and air atmospheres at heating rates of 5, 10, 20, and 40 °C min⁻¹. Thermal profiles revealed three degradation stages: moisture loss (30–150 °C), main-chain scission and depolymerization (150–450 °C), and carbonaceous residue formation (>450 °C), with the principal decomposition peak at 370–410 °C. Activation energies (Eₐ) determined using Kissinger, Flynn–Wall–Ozawa (FWO), and Kissinger–Akahira–Sunose (KAS) methods ranged from 179 to 186 kJ mol⁻¹ and were validated using the Coats–Redfern model-fitting approach. Reaction orders (n ≈ 1.1–1.3) indicate random chain scission as the dominant mechanism. The resulting kinetic dataset provides reliable insight into PVP thermal stability and supports optimization of processing, recycling, and composite fabrication.